Coronavirus-related health literacy level of Turkish adults: psychometric properties of the scale - Soylar, Pinar; Ozturk, Fatma Ozlem; Sonmez, Sibel (Oxford Univ Press, 2024)
An adequate level of health literacy enables people to adopt protective behaviors to cope with the COVID-19 pandemic. Validated instruments are desired to assess such reactions. This study aims to determine the level of health literacy and validity and reliability of the Coronavirus-Related Health Literacy Questionnaire (HLS-COVID-Q22) adapted to Turkish. The present study was carried out with 452 participants in Turkey using an online survey. The scale was translated from English to Turkish using the back-translation technique. The cultural adaptation was outlined in the context of establishing the validity and reliability of the instruments. A coronavirus-related health literacy measure was validated (HLS-COVID-Q22) for the Turkish population through exploratory factorial analysis, followed by a confirmatory factorial analysis. The coronavirus-related health literacy level of the participants was found to be 2.92 (+/- 0.51). Cronbach's alpha internal consistency coefficient was found to be 0.95. A four-factor solution was confirmed with eigenvalues > 1.0, suggesting a four-factor solution and explaining 68.84% of the total variance. It was determined that the chi(2)/df and root mean square residual, root mean square error of approximation and comparative fit index values in the last model had a good fit and that the normed fit index, goodness-of-fit index and adjusted goodness-of-fit index values were acceptable. The coronavirus-related health literacy level of Turkish adults was moderate. HLS-COVID-Q22 was a reliable and valid instrument for measuring coronavirus-related health literacy in the Turkish population. Promoting population-based health literacy and making decisions on accurate and reliable information are important in coping with the epidemic.
Keywords: health literacy; infodemic; coronavirus; COVID-19; Turkish adult population